Strain-specific consumption and transformation of alga-derived dissolved organic matter by members of the Limnohabitans-C and Polynucleobacter-B clusters of Betaproteobacteria - Horňák, Karel; Kasalický, Vojtěch; Šimek, Karel; Grossart, Hans-Peter (Environmental microbiology, 2017)
We investigated changes in quality and quantity of extracellular and biomass-derived organic matter (OM) from three axenic algae (genera Rhodomonas, Chlamydomonas, Coelastrum) during growth of Limnohabitans parvus, Limnohabitans planktonicus and Polynucleobacter acidiphobus representing important clusters of freshwater planktonic Betaproteobacteria. Total extracellular and biomass-derived OM concentrations from each alga were approximately 20 mg l-1 and 1 mg l-1 respectively, from which up to 9% could be identified as free carbohydrates, polyamines, or free and combined amino acids. Carbohydrates represented 54%-61% of identified compounds of the extracellular OM from each alga. In biomass-derived OM of Rhodomonas and Chlamydomonas 71%-77% were amino acids and polyamines, while in that of Coelastrum 85% were carbohydrates. All bacteria grew on alga-derived OM of Coelastrum, whereas only Limnohabitans strains grew on OM from Rhodomonas and Chlamydomonas. Bacteria consumed 24%-76% and 38%-82% of all identified extracellular and biomass-derived OM compounds respectively, and their consumption was proportional to the concentration of each OM compound in the different treatments. The bacterial biomass yield was higher than the total identifiable OM consumption indicating that bacteria also utilized other unidentified alga-derived OM compounds. Bacteria, however, also produced specific OM compounds suggesting enzymatic polymer degradation or de novo exudation.
Keywords: sacharidy; aminokyseliny; Amino Acids; sladká voda; plankton; polyaminy; Carbohydrate Metabolism; Cryptophyta; Biomass; Burkholderiaceae; Chlorophyta; Carbohydrates; Fresh Water; Plankton; Comamonadaceae; metabolismus sacharidů; biomasa; Polyamines